2008
DOI: 10.3892/ijmm.21.2.145
|View full text |Cite
|
Sign up to set email alerts
|

CDC25A inhibition suppresses the growth and invasion of human hepatocellular carcinoma cells

Abstract: Abstract. CDC25A is a cell cycle-activating phosphatase that promotes transition from the G1 to S phase. We previously reported that overexpression of CDC25A in human hepatocellular carcinoma (HCC) tissue samples was associated with poor prognosis. In this study, we attempted suppression of CDC25A in HCC cells to elucidate the therapeutic potential of this approach. Administration of CDC25A antisense (AS) oligonucleotide resulted in 25-50% inhibition of cell growth at 48 h, G0-G1 arrest, and significant inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Silencing the CDC25A gene significantly inhibited the growth of the xenograft tumors (P<0.05), indicating that cdc25A is a key gene in the development of liver cancer. Xu et al (32) produced a study that used cdc25A antisense to inhibit cdc25A in liver cancer cells, and revealed that cell growth, invasion and cell cycle were inhibited, which was consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Silencing the CDC25A gene significantly inhibited the growth of the xenograft tumors (P<0.05), indicating that cdc25A is a key gene in the development of liver cancer. Xu et al (32) produced a study that used cdc25A antisense to inhibit cdc25A in liver cancer cells, and revealed that cell growth, invasion and cell cycle were inhibited, which was consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, overexpression of CDC25B in the mammary glands of mice increases the proliferation of mammary epithelial cells and hyperplasia, which induces tumor growth when also challenged with the carcinogen 9,10-dimethyl-1,2-benzanthracene [7,8] . Conversely, downregulating the expression of CDC25B by microinjecting antibodies against CDC25B causes G2 arrest, whereas RNA interference against CDC25A causes G1 arrest and significant inhibition of cancer cell invasion [9,10] . These findings in turn make CDC25 A and B ideal targets for a new anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…CDC25a, a member of the CDC25 family of phosphatases, is required for progression from G1 to the S phase of the cell cycle [51, 52]. Interfering with CDC25a suppresses the growth and invasion in tumor cells [51, 53, 54]. Our results indicated that enforced LRRC4 expression prevents the activation of ERK downstream transcription factors to inhibit glioblastoma cell proliferation and invasion.…”
Section: Discussionmentioning
confidence: 76%